Attempt for Settlement of Dispute for Tax Billing at ADHI-IBG, KSO Batang Bayang Project - Wellia Novita; Puspita Rama Nopiana; Yohan Fitriadi (ProBisnis : Jurnal Manajemen, 2023)
This paper is motivated by the Tax Bill, which states that the application letter for term payment includes billing documents that should not be part of it. This article discusses efforts to resolve tax disputes over tax restitution at ADHI-IBG, KSO Batang Shadow Project. This article is normative legal research, which explains the understanding of legal issues holistically and the methods used qualitatively descriptive. The result was submitted that WP filed a lawsuit through an appeal to the Tax Court. Tax taxpayers assume that the inspector needs to be more accurate in determining the sanctions or fines listed on the Tax Bill. As a result of this tax dispute resolution effort, WP's objection was approved, and it was decided that WP should not pay the fines or penalties issued by DJP. The level of dispute resolution efforts is WP compliance that must be appreciated; because it has obeyed the rules and completed its obligations, WP must prioritize the principle of justice following applicable regulations.